Electronics Explained Fundamentals for Engineers, Technicians, and Makers - Frenzel, Louis E.; Frenzel, Louis E. (Newnes, 2017)
Electronics Explained, Second Edition, takes a systems based approach to the fundamentals of electronics, covering the different types of electronic circuits, how they work, and how they fit together to create modern electronic equipment, enabling you to apply, use, select, operate and discuss common electronic products and systems. This new edition has been updated to show the latest technological trends with added coverage of: - Internet of Things (IoT) - Machine-to-Machine (M2M) technology - Ethernet to 100 Gb/s - Wi-Fi, Bluetooth and other wireless technologies - 5G New Radio cellular standards - Microcontrollers and programming with the Arduino, BASIC Stamp and others - Learn about the basic components of electronics such as resistors, capacitors, inductors, transformers, diodes, transistors, and integrated circuits - Discover different types of circuits, using the functional block diagram approach which makes it easy to understand their purpose and application - Get involved with Hands-On projects in each chapter, using components and ICs with the breadboarding socket